the Implementation of Madrasah Curriculum Quality Standards and the Challenges in Improving the Quality of Islamic Education: The Concept of Madrasah Curriculum Quality Standards - Dwi Agustin; Triwid Syafarotun Najah; Dakir Dakir (Jurnal Kajian Islam dan Sosial Keagamaan, 2026)
The curriculum is one of the key components of the educational system and plays a vital role in determining the quality of the learning process and outcomes. In the context of Islamic education, madrasahs are required to implement curriculum quality standards that integrate Islamic values with the demands of advances in science and technology, as well as the needs of society. This study aims to describe the implementation of curriculum quality standards in madrasahs, identify the various problems encountered in their implementation, and analyze efforts that can be undertaken to improve the quality of Islamic education through the effective application of curriculum quality standards. The research method used was a literature review (library research), involving the collection and analysis of various scholarly sources, including books, journals, articles, and regulations, and documents related to curriculum quality standards and Islamic education. The data were analyzed using qualitative descriptive analysis techniques to gain a comprehensive understanding of the implementation and challenges of curriculum quality standards in madrasahs. The results of the study indicate that the implementation of madrasah curriculum quality standards plays a strategic role in improving the quality of Islamic education through targeted curriculum planning, implementation, and evaluation.